The Metabolic Syndrome and Mind-Body Therapies: A Systematic Review - Joel G. Anderson; Ann Gill Taylor (Journal of Nutrition and Metabolism)
The metabolic syndrome, affecting a substantial and increasing percentage of the worldwide population, is comprised of a cluster of symptoms associated with increased risk of type 2 diabetes, cardiovascular disease, and other chronic conditions. Mind-body modalities based on Eastern philosophy, such as yoga, tai chi, qigong, and meditation, have become increasingly popular worldwide. These complementary therapies have many reported benefits for improving symptoms and physiological measures associated with the metabolic syndrome. However, clinical trial data concerning the effectiveness of these practices on the syndrome as a whole have not been evaluated using a systematic and synthesizing approach. A systematic review was conducted to critically evaluate the data from clinical trials examining the efficacy of mind-body therapies as supportive care modalities for management of the metabolic syndrome. Three clinical trials addressing the use of mind-body therapies for management of the metabolic syndrome were identified. Findings from the studies reviewed support the potential clinical effectiveness of mind-body practices in improving indices of the metabolic syndrome.